Spleno-adrenal fusion mimicking an adrenal metastasis of a renal cell carcinoma: A case report and embryological background - Tüdös Zbyněk (De Gruyter, 2020)
Foci of splenic tissue separated from the spleen can occur as a congenital anomaly. Isolated nodules of splenic tissue are called accessory spleens or spleniculli. However, nodules of splenic tissue can merge with other organs during embryonic development, in which case we speak of spleno-visceral fusions: most often, they merge with the tail of the pancreas (thus forming spleno-pancreatic fusion or an intrapancreatic accessory spleen), with the reproductive gland (i.e., spleno-gonadal fusion), or with the kidney (i.e., spleno-renal fusion). Our case report describes the fusion of heterotopic splenic tissue with the right adrenal gland, which was misinterpreted as a metastasis of a renal cell carcinoma. To the best of our knowledge, this is the first reported case of spleno-adrenal fusion. Spleno-visceral fusions usually represent asymptomatic conditions; their main clinical significance lies in the confusion they cause and its misinterpretation as tumors of other organs. We believe that the cause of retroperitoneal spleno-visceral fusions is the anomalous migration of splenic cells along the dorsal mesentery to the urogenital ridge, together with primitive germ cells, at the end of the fifth week and during the sixth week of embryonic age. This theory explains the possible origin of spleno-visceral fusions, their different frequency of occurrence, and the predominance of findings on the left side.